2019
DOI: 10.31234/osf.io/dxfkj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing a gambling warning label’s effect on behavior

Abstract: Responsible gambling campaigns are one measure enacted by a number of statutory bodies and gambling operators in response to concerns about gambling marketing and the accessibility of modern gambling products. For example, since 2015 a number of the UK‘s largest gambling operators have attached the following warning label to TV and shop window adverts: "when the FUN stops, stop" (where the word "fun" is printed in noticeably larger font than any other word). Here we present an initial independent test of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Therefore, Parke et al (2014) suggest that this information is displayed asynchronously rather than at the same time as the advertisements. Newall et al (2019) found that the "When the FUN stops, stop gambling" warning messages (which are presented alongside sports betting advertisements on online gambling operator's websites) did not have a significant effect on gambling behavior. However, further empirical research is required in order to examine the impact of responsible gambling campaigns on different media sources, for example, television advertisements.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, Parke et al (2014) suggest that this information is displayed asynchronously rather than at the same time as the advertisements. Newall et al (2019) found that the "When the FUN stops, stop gambling" warning messages (which are presented alongside sports betting advertisements on online gambling operator's websites) did not have a significant effect on gambling behavior. However, further empirical research is required in order to examine the impact of responsible gambling campaigns on different media sources, for example, television advertisements.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, these promotions may be initiating online impulse gambling behavior. The uptake of wagering inducements has been previously found to predict impulse betting among problem gamblers and frequent sports viewers (Hing et al 2018) and gambling operators will often advertise recently "improved" or "flash odds," sometimes with a reduced time-frame, which makes the bet appear more urgent (Newall et al 2019). The present exploratory study found these promotions appeared to change betting behavior, but further research is required to examine how such promotions change betting behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This specific message was identified in approximately two-fifths of the advertising sample utilised by Critchlow et al [ 54 ]. A recent study of 3000 gamblers, indicated that this particular message either showed no beneficial effect of curtailing gambling behaviour or produced a backfire effect that influenced increased betting participation [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some warning labels are extremely generic (e.g., in Australia, 'Gamble responsibly'; in the UK, 'When the fun stops, stop'; or in Ontario, 'Play smart'). These labels provide little information to meaningfully guide consumers (Newall et al, 2019c) and might be ignored due to sheer repetition of content (Lole et al, 2019). Other gambling warning labels warn gamblers only about the product they are currently using, an approach that has been most consistently applied to electronic gambling machines (Wohl et al, 2014;Ginley et al, 2017;McGivern et al, 2019).…”
Section: Introductionmentioning
confidence: 99%